2022
DOI: 10.1038/s41586-022-05534-y
|View full text |Cite|
|
Sign up to set email alerts
|

Microglia regulate central nervous system myelin growth and integrity

Abstract: Myelin is required for the function of neuronal axons in the central nervous system, but the mechanisms that support myelin health are unclear. Although macrophages in the central nervous system have been implicated in myelin health1, it is unknown which macrophage populations are involved and which aspects they influence. Here we show that resident microglia are crucial for the maintenance of myelin health in adulthood in both mice and humans. We demonstrate that microglia are dispensable for developmental my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
127
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 191 publications
(141 citation statements)
references
References 52 publications
12
127
0
2
Order By: Relevance
“…The central nervous system currently consists of three major cell types: neurons, astrocytes, and microglia [ 41 , 42 ]. Currently, microglia are reported to be mainly involved in immune function; the excessive release of pro-inflammatory factors and gasdermin activation in microglia will lead to the pyroptosis of the whole nervous system [ 43 , 44 ]. In the present study, evidence showed that only GSDME is expressed in hippocampal neuronal cells, not GSDMD.…”
Section: Discussionmentioning
confidence: 99%
“…The central nervous system currently consists of three major cell types: neurons, astrocytes, and microglia [ 41 , 42 ]. Currently, microglia are reported to be mainly involved in immune function; the excessive release of pro-inflammatory factors and gasdermin activation in microglia will lead to the pyroptosis of the whole nervous system [ 43 , 44 ]. In the present study, evidence showed that only GSDME is expressed in hippocampal neuronal cells, not GSDMD.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is possible that low SES might be related to neuroinflammation via obesity incidence. Additionally, microglia dysregulation may cause myelin damage 80,81 , which could explain the observed association between obesity and RSI-RND. Second, because RSI-RNI increases with normative child development 36 , our findings of greater RSI-RNI, which were corrected for age, may represent accelerated white matter maturation with socioeconomic disadvantage.…”
Section: Discussionmentioning
confidence: 99%
“…Impairment of normal microglial function causes serious effects on normal brain development. MG also regulates myelin growth and integrity in the CNS [ 165 ]. MG interacts with neurons and modulates neuronal activity [ 166 ].…”
Section: Conventional and Novel Targets For Slowing And/or Preventing...mentioning
confidence: 99%